A South African national database in cardiothoracic surgery - Linegar, Anthony (Clinics Cardive Publishing, 2010)
SUMMARY: This article aims to update South African cardiothoracic surgeons on the developmental progress of the national database in cardiac and thoracic surgery and to encourage participation in this most important endeavour.